2023
DOI: 10.3389/fendo.2023.1141605
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of frozen-thaw blastocyst transfer strategies in women aged 35–40 years: a retrospective study

Abstract: ObjectiveTo compare the effects of five different frozen-thaw embryo transfer (FET) strategies in women aged 35–40 years.MethodsData from 1,060 patients were divided into five groups according to the number and quality of transferred blastocysts: a high-quality single blastocyst group (group A, n= 303), a high-quality double blastocysts group (group B, n= 176), a high-quality plus poor-quality double blastocysts group (group C, n= 273), a poor-quality double blastocysts group (group D, n= 189), and a poor-qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…Age is one of the most important factors in choosing an embryo transfer strategy. A meta-analysis showed that high-quality SET is the first choice for women under 40 years of age [ 10 ], which coincides with previous studies by our team [ 4 , 5 ]. However, some studies suggest that the best pregnancy outcomes can be obtained by transferring a single blastocyst in individuals under 35 years old and 35–37 years old; while, for individuals aged 38–40 years and older, DET has better perinatal outcomes than SET [ 11 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Age is one of the most important factors in choosing an embryo transfer strategy. A meta-analysis showed that high-quality SET is the first choice for women under 40 years of age [ 10 ], which coincides with previous studies by our team [ 4 , 5 ]. However, some studies suggest that the best pregnancy outcomes can be obtained by transferring a single blastocyst in individuals under 35 years old and 35–37 years old; while, for individuals aged 38–40 years and older, DET has better perinatal outcomes than SET [ 11 ].…”
Section: Discussionsupporting
confidence: 87%
“…Our team previously conducted a study on the number and type of blastocysts transferred and found that high-quality SBT was the optimal frozen-thawed embryo transfer (FET) strategy for young women [ 4 ]. Although this strategy is still feasible for patients aged 35–40 years [ 5 ], there were some limitations in the previous study; for example, women of advanced age were not stratified, and it is impossible to determine whether the benefits of SBT are the same for women aged 35–37 years and older. To our knowledge, no studies have explored on age stratification in frozen-thawed high-quality SBT.…”
Section: Introductionmentioning
confidence: 99%